The Analysis Study of The Effect Vitamin D to Risk for Type 2 Diabetes Mellitus in People with Pre-Diabetes : A Comprehensive Systematic Review - Novriadi, Dodi; Christoper, Woris (The International Journal of Medical Science and Health Research, 2024)
Background: Individuals with prediabetes are at a 50% increased risk of advancing to Type 2 Diabetes Mellitus (T2DM). Deficient levels of vitamin D are associated with higher risks of insulin resistance and diabetes. Methods: This systematic review adhered to PRISMA 2020 guidelines, focusing exclusively on full-text articles published in English between 2012 and 2024. Result: The review process involved analyzing over 300 publications from the selected databases. After an initial screening, eight studies met the criteria for detailed examination. These studies underwent an in-depth review to ensure a rigorous and comprehensive evaluation of their findings. Conclusion: Vitamin D supplementation may offer potential benefits in reducing the risk of T2DM in individuals with prediabetes by enhancing insulin synthesis and sensitivity. However, the overall effectiveness of diabetes prevention is still debated, with recent large-scale trials reporting nonsignificant results. The fat-soluble nature of vitamin D may limit its effectiveness in obese individuals. The American Diabetes Association advocates for further research to explore the potential advantages of combining vitamin D supplementation with lifestyle interventions.